2014
DOI: 10.1002/ejoc.201301762
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Indoles by Domino Reaction of 2‐(Tosylamino)benzyl Alcohols with Furfurylamines: Two Opposite Reactivity Modes of the α‐Carbon of the Furan Ring in One Process

Abstract: An unusual domino reaction where the same furan α‐carbon atom reacts initially as a nucleophile and then as an electrophile is reported. In the presence of acid, N‐tosylfurfurylamines react with 2‐(tosylamino)benzyl alcohols to afford 2‐(2‐acylvinyl)indoles. The reaction proceeds by Friedel–Crafts alkylation at the C(2) atom of furan followed by acid‐catalyzed intramolecular nucleophilic attack of the ortho‐amino group onto the same carbon atom. The replacement of the tosylamino leaving group by phthalimide en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Thus, when we used furfurylamine 1f , containing a 4-F 3 CC 6 H 4 group at this position, the target pyrrolo­[1,2- a ]­[1,4]­diazepin-3­(2 H )-ones 5j,k were obtained in low yields only. This is definitely resulted from the easy C–N bond cleavage producing persistent α-substituted furfuryl cation that induced diverse side processes. , …”
Section: Results and Discussionmentioning
confidence: 99%
“…Thus, when we used furfurylamine 1f , containing a 4-F 3 CC 6 H 4 group at this position, the target pyrrolo­[1,2- a ]­[1,4]­diazepin-3­(2 H )-ones 5j,k were obtained in low yields only. This is definitely resulted from the easy C–N bond cleavage producing persistent α-substituted furfuryl cation that induced diverse side processes. , …”
Section: Results and Discussionmentioning
confidence: 99%
“…( E )‐4‐(3‐Phenyl‐1‐tosyl‐1 H ‐indol‐2‐yl)but‐3‐en‐2‐one (( E )‐2 a) [18] was synthesized according to the reported procedure [7] …”
Section: Methodsmentioning
confidence: 99%
“…(Z)-4-(3-Phenyl-1-tosyl-1H-indol-2-yl)but-3-en-2-one (2 a) was synthesized according to the reported procedure. [7] (E)-4-(3-Phenyl-1-tosyl-1H-indol-2-yl)but-3-en-2-one ((E)-2 a) [18] was synthesized according to the reported procedure. [7] Synthesis of (E)-4-(3-Phenyl-1H-indol-2-yl)but-3-en-2-one (3).…”
Section: General Informationmentioning
confidence: 99%
“…Very recently, Uchuskin et al reported two opposite reactivity modes of the a-carbon of the furan ring in one process and synthesized various 2-(2-acetylvinyl)indoles derivatives 168 by domino reaction of N-tosylfurfurylamine 167 with 2-tosylaminobenzyl alcohols 142 (Scheme 40). 129 The a-carbon of the furan behaves unusually, which reacts initially as a nucleophile in the Friedel-Cras alkylation and then as an electrophile in the Piancatelli-like rearrangement, followed by aromatization of the rearranged product. When the tosylamino group in the furan side chain of 167 was substituted by the phthalimide moiety chemoselectivity of the reaction changes and exclusively gave A. Srivastava et al used commercially available inexpensive (AE)-CSA (30 mol%) as a Brønsted acid for domino dehydration/ condensation/cyclization sequence reaction for the synthesis of substituted indole derivatives.…”
Section: Table 7 Synthesis Of Various Dihydropyrroles and Pyrrolesmentioning
confidence: 99%